Analisis Laporan Sisa Hasil Usaha (SHU) Pada Koperasi Unit Desa (KUD) Mandiri Bangkit Jaya Kabupaten Subang - Sakti Muda Nasution (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
Analysis of Remaining Business Results (SHU) at the Village Unit Cooperative (KUD) Mandiri Bangkit Jaya Subang Regency 2015-2019. This study aims to analyze the remaining business results (SHU) of the cooperative which is used to assess the financial performance of the Village Unit Cooperative (KUD) Mandiri Bangkit Jaya, Subang Regency. This research is descriptive quantitative research. The population in this study is the entire financial report of the Village Unit Cooperative (KUD) Mandiri Bangkit Jaya District of Subang for the last 5 (five) years 2015-2019, while the sample in this study is the balance sheet and calculation of the remaining business results (SHU) for 5 (five) the last year 2015-2019. The data analysis technique used is the horizontal technique and the vertical technique. The research findings show that the achievement of remaining business results (SHU) obtained by the Village Unit Cooperative (KUD) Mandiri Bangkit Jaya in the Subang Regency during the last 5 (five) periods, namely the 2015-2019 period, shows good achievement. Based on the results of the analysis of vertical techniques and horizontal techniques, the cooperative's remaining operating income (SHU) has increased every period. Based on the percentage of own capital and fixed assets owned by the cooperative, the financial performance of the Village Unit Cooperative (KUD) Mandiri Bangkit Jaya in Subang Regency for the last 5 (five) years, namely the 2015-2019 period showed good performance.